Expansion of higher education, employment and wages: Evidence from the Russian transition - Natalia Kyui (Bank of Canada, 2013)
This paper analyzes the effects of an educational system expansion on labour market outcomes, drawing upon a 15-year natural experiment in the Russian Federation. Regional increases in student intake capacities in Russian universities, a result of educational reforms, provide a plausibly exogenous variation in access to higher education. Additionally, the gradual nature of this expansion allows for estimation of heterogeneous returns to education for individuals who successfully took advantage of increasing educational opportunities. Using simultaneous equations models and a nonparametric model with essential heterogeneity, the paper identifies strong positive returns to education in terms of employment and wages. Marginal returns to higher education are estimated to decline for lower levels of individual unobserved characteristics that positively influence higher education attainment. Finally, the returns to higher education are found to decrease for those who, as a result of the reforms, increasingly pursued higher education.
Keywords: J24; I20; 330; Labour markets; Development economics